2012
DOI: 10.1128/aac.06009-11
|View full text |Cite
|
Sign up to set email alerts
|

PXR Variants and Artemisinin Use in Vietnamese Subjects: Frequency Distribution and Impact on the Interindividual Variability of CYP3A Induction by Artemisinin

Abstract: f Artemisinins induce drug metabolism through the activation of the pregnane X receptor (PXR) in vitro. Here, we report the resequencing and genotyping of PXR variants in 75 Vietnamese individuals previously characterized for CYP3A enzyme activity after artemisinin exposure. We identified a total of 31 PXR variants, including 5 novel single nucleotide polymorphisms (SNPs), and we identified significantly different allele frequencies relative to other ethnic groups. A trend of significance was observed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Moreover, the PXR*1B haplotype, which is tagged by the SNPs 2654T > C and IVS6-17C > T, was related to doxorubicin clearance in Asian breast cancer patients (Sandanaraj et al, 2008). Further studies analyzing patient cohorts under fosamprenavir/lopinavir or artemisinin treatment gave additional hints to some PXR variants that may affect inducibility of CYP3A4 phenotype expression (Svärd et al, 2010; Piedade et al, 2012). The occurrence of two SNPs in the 3′UTR region of PXR , rs3732359 and rs3732360, has been shown to be associated with altered midazolam 1′-hydroxylation in a liver bank and with more pronounced effect in midazolam clearance of healthy volunteers of African American descent (Oleson et al, 2010).…”
Section: Genes Influencing Cyp3a4 Phenotype Outside the Cyp3a Locusmentioning
confidence: 99%
“…Moreover, the PXR*1B haplotype, which is tagged by the SNPs 2654T > C and IVS6-17C > T, was related to doxorubicin clearance in Asian breast cancer patients (Sandanaraj et al, 2008). Further studies analyzing patient cohorts under fosamprenavir/lopinavir or artemisinin treatment gave additional hints to some PXR variants that may affect inducibility of CYP3A4 phenotype expression (Svärd et al, 2010; Piedade et al, 2012). The occurrence of two SNPs in the 3′UTR region of PXR , rs3732359 and rs3732360, has been shown to be associated with altered midazolam 1′-hydroxylation in a liver bank and with more pronounced effect in midazolam clearance of healthy volunteers of African American descent (Oleson et al, 2010).…”
Section: Genes Influencing Cyp3a4 Phenotype Outside the Cyp3a Locusmentioning
confidence: 99%
“…PXR and CAR are transcriptional regulators of a wide range of genes whose products metabolise a wide range of drugs [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, NR1I2 (rs13059232) was found to affect the occurrence of CR in IS patients treated with clopidogrel [28]. Studies have shown that the expression levels of NR1I2 could be affected by gene polymorphisms of NR1I2, which could further influence the activities of downstream metabolic enzymes and transporters [20,21]. For example, it was reported that NR1I2 (rs13059232) influences the phenotypes of CYP3A4 [29], an important enzyme that metabolizes clopidogrel.…”
Section: Discussionmentioning
confidence: 97%
“…NR1I2 genetic polymorphisms have a significant impact; specifically, they affect the uptake, transport, and metabolism of various endogenous and exogenous substances. Therefore, NR1I2 genetic polymorphisms are of great significance in studying the metabolic processing of clinical drugs [20,21]. Nevertheless, research on the relationship between the genetic polymorphisms of NR1I2 and individual differences in the therapeutic effects of clopidogrel is currently limited.…”
Section: Introductionmentioning
confidence: 99%